A Multimodal Approach to Image Sentiment Analysis - Gaspar, António (2020)
Multimodal sentiment analysis is a process for the classi- cation of the content of composite comments in social media at the sentiment level that takes into consideration not just the textual content but also the accompanying images. A composite comment is normally represented by the union of text and image. Multimodal sentiment analysis has a great dependency on text to obtain its classi cation, because image analysis can be very subjective according to the context where the image is inserted. In this paper we propose a method that reduces the text analysis dependency on this kind of classi cation giving more importance to the image content. Our method is divided into three main parts: a text analysis method that was adapted to the task, an image classi er tuned with the dataset that we use, and a method that analyses the class content of an image and checks the probability that it belongs to one of the possible classes. Finally a weighted sum takes the results of these methods into account to classify content according to its sentiment class. We improved the accuracy on the dataset used by more than 9%.